New illustration for Mixed Mode Fracture Mechanics Analysis of Central-Crack Plates Using Crack Extension Technique and Matlab - Nassar, Ameen Ahmed (Basrah Journal for Engineering Sciences, 2013)
New illustration for mixed mode fracture mechanics analysis of central cracked plates using crack extension technique and Matlab Environment is presented. The technique of crack extension is applied to the computation of mixed mode stress intensity factors in linear elastic fracture mechanics for these plates for different loads. The technique uses the Brown approximate solutions for stress intensity factors and the Westergaard analytical solutions for stress and displacement near a crack tip in finite plate to calculate crack extension during each load step using an proved to be a good tool for computation and results illustration for mixed mode stress intensity factors. The results were illustrated in a new form which is convenient for engineers and fracture mechanics analyst. The developed procedure reduced the need for sophisticated numerical analyses, which require more time and effort, to calculate the same parameters tackled in this research.